Factors influencing atrophy progression in primary progressive aphasia. (December 2021) - Lombardi, Jolina; Mayer, Benjamin; Huppertz, Hans‐Jürgen; Straub, Sarah; Semler, Elisa; Uttner, Ingo; Kassubek, Jan; Diehl‐Schmid, Janine; Danek, Adrian; Levin, Johannes; Fassbender, Klaus; Fliessbach, Klaus; et al.
Abstract: Background: Primary progressive aphasia (PPA) is a rare primarily language‐related neurodegenerative disorder that subdivides into the non‐fluent (nfvPPA) and the semantic variant (svPPA). Atrophy progression shows variant‐specific patterns, however, its extent seems highly individual and thus difficult to predict. Method: We investigated volumetric changes in patients with nfvPPA (n=18) and svPPA (n=15) with an MRI scan (3D T1 MPRAGE sequence, 3T) at baseline and 2‐years follow‐up that were recruited from the prospective German FTLD‐consortium study. According to the LONI Probabilistic Brain Atlas (Shattuck et al., 2009), 56 brain regions were assessed with automated atlas‐based volumetry (Huppertz et al., 2010). Longitudinal volumetric changes were analyzed by means of the R software (www.r‐project.org ). A possible impact of group, adjusted for age and sex, had been investigated using a linear mixed effect model. Atrophy progression for each region over two years was correlated (Pearson or Kendall rank correlation; 95% BCa bootstrap CI with 1000 replicates) with age at symptom onset, years of education, and disease duration to review a possible relation. Result: Volume change within 2‐years revealed parts of the left frontal lobe (up to ‐10%) and subcortical regions in nfvPPA and parts of the left temporal lobe (up to ‐15%) and the hippocampus/amygdala complex in svPPA as most progressive. A correlation analysis with age at symptom onset rendered no relevant results. Higher educated patients showed more atrophy in the right parahippocampal gyrus in nfvPPA and less atrophy in white matter portions of the left superior frontal, the bilateral middle and inferior frontal, the right middle and bilateral lateral orbitofrontal and the bilateral cingulate gyrus in svPPA. Shorter disease duration correlated with higher atrophy in the caudate and putamen in nfvPPA, and in the left middle and inferior temporal gyrus, the right superior and bilateral middle occipital gyrus, the left cuneus, and left angular gyrus in svPPA. Conclusion: Age at symptom onset showed no interrelation with atrophy progression in PPA. Higher education levels seem to slow white matter decrease of frontal areas in svPPA. Shorter disease duration is related to increased volume loss in some primarily affected regions in both nfvPPA and svPPA.